CONCEPTUAL PRINCIPLES OF FORMING OF MULTIMODAL SYSTEM TRANSPORTATION LOADS - Соколова, О. Є. (Science-based technologies, 2014)
Essence of the multimodal cargo transportation system is exposed in the article. It is set that the multimodal cargo transportation system shows integrated associate transport system, the functional task of that is an acceleration, reduction of prices and simplification of technological procedures during the complete chain of delivery "from door to the door" on the terms of organizational and technical cooperation of all transportation process branches. The specific of the multimodal cargo transportation system functioning is considered. It is determined that the multimodal cargo transportation system is based on internal integration of different transport modes and other transportation process participants, that co-operate inter se, and also execute the part of work within the limits of contractual relations and at presence of only organ of management – to the operator transport-logistic services. It is proved that a basic task in the process of the multimodal transportation system forming is complex development of all its subsystems and elements. The basic stages are worked out to forming and development of the multimodal cargo transportation system. It is proven that the multimodal cargo transportation system assists the unitization of the trade-legal mode, allows complex approach of the financial and problems solutions, providing the permanent functioning of the system. Also it allows co-ordination, organizational and technological cooperation of all elements of cargo delivery chain, assists to complex development of infrastructure and different transport modes resources.